BROILER CARCASSES PIECES GIVEN A RATIONS OF FERMENTED LIGNOCELLULOLYTIC PROBIOTIC BACTERIA - N. K., Risnayanti; Mudita, I M.; Puger, A. W. (Jurnal Peternakan Tropika; Vol 11 No 1 (2023): Vol. 11 No. 1 Tahun 2023; January - april, 2023)
This study aims to determine the effect of fermented rations with lignocellulolytic probiotic bacteria on the production of broiler carcass pieces. The design used was a completely randomized design (CRD), with 5 treatments, 4 replications and each replication consisted of 3 chickens. The treatments were broilers given commercial rations (RK), fermented rations without lignocellulolytic probiotic bacteria (RF0), fermented rations with 5% Bacillus subtilis BR4LG (RF1), fermented rations with 5% Bacillus sp. BT3CL (RF2) and fermented rations with 5% Bacillus sp. BT8XY (RF3). The variables observed were carcass weight, carcass percentage and carcase pieces percentage (chest, back, wings, thighs and calves). The results showed that the treatment of RF1, RF2 and RF3 resulted in higher carcass weight and chest percentage (P<0.05), but the percentage of back, wings and thighs was not significantly (P>0.05) with RF0 treatment. When compared with the RK treatment, RF0, RF1, RF2 and RF3 treatments produced carcass weight, chest and thigh percentages that were significantly different (P>0.05) lower and resulted in significantly different back and wing percentages (P>0.05) higher than the RK treatment. Based on the results of the study, it can be concluded that the fermented ration of lignocellulolytic probiotic bacteria as much as 5% can increase carcass weight and breast percentage, but has not been able to increase the percentage of back, wings and thighs of broilers from fermented ration treatment without lignocellulolytic bacteria. When compared with the provision of commercial rations, fermented rations resulted in lower carcass weight, lower chest and thigh percentages and higher back and wing percentages. Keywords: broiler, lignocellulolytic probiotic bacteria, carcass pieces